PERKEMBANGAN PERSURATKABARAN DI RIAU MASA REFORMASI (1998-2015) - Aryanti, Ayu; Ibrahim, Bedriati; ', Bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: 1998 is a new milestone for the growth of the struggle Indonesian press, along with opening of the door of reform to establish a new political partai, the print media emerged and grow very rapidly. Developments in Riau newspaper can thrive well in compasison the new orde only one daily newspaper (Riau Pos) and one weekly newspaper (Genta) are active today orde of print media to survive until now. In 2004 Riau own 60 poblications includding approximately is daily, 35 weekly and tabloid magazine and newspaper as well as a number of camps. This study aims to determine (1) the development of newspaper before the reform period in riau. (2) to asess progress of newpaper reform period in riau. (3) The character of Riau press figure. (4) the impact of press freedom in Riau. As for this research uses qualitative research method to approach history and data collection techniques in the form of literature, observation, documentation and interview. This study has shown that development of newspaper in Riau reform period has developed very well which is caused because the press get legal recognition 40 of 1999 of the press.Key Words: Reform, Newspaper